Impact of addition of different carbon and nitrogen sources on solubilization of rock phosphate by phosphate-solubilizing micro-organisms - VORA, V S; SHELAT, H N (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during 1996-97 at Anand to study the effect of different sources of carbon and nitrogen on solubilization of rock phosphate by different selected strains of phosphate-solubilizing micro-organisms, viz Bacillus circilans, Bacillus brevis, Bacillus coagulans and Torulospora globosa. Among different carbon sources, maximum solubilization was observed in glucose, sucrose and fructose. None of the organisms could utilize rock phosphate in presence of maltose. Among different sources of nitrogen, ammonium sulphate was the best source for all bacterial strains examined, however it was poorly utilized by the yeast. None of the strains could successfully utilize sodium nitrate. Torulospora globosa preferred calcium nitrate as nitrogen source.